Musculoskeletal disorders in diabetes mellitus - E. A. Balakhonova (Сахарный диабет)
The increased prevalence of musculoskeletal diseases is most often observed in diabetes mellitus (DM) compared to the general population. This is a common cause of disability. DM affects on all components of the musculoskeletal system, namely: muscles, bones and connective tissue. One of the unique diseases that occur only in humans with DM is diabetic myonecrosis. Other pathological conditions include: diabetic amyotrophia, adhesive capsulitis, diabetic cheiropathy, Dupuytren contracture, stenosing tendovaginitis of flexors, carpal tunnel syndrome, diabetic osteoarthropathy and others. Some of the complications have a known direct link to DM, while others have a suspected but unproven link. Musculoskeletal complications in people with DM receive less attention than life-threatening microvascular or macrovascular complications. However, these complications are underestimated and can lead to significant consequences. This review systematizes the prevailing knowledge about the influence of DM on the pathologies of the musculoskeletal system and the main mechanisms that underlie these disorders. The rest of the article is devoted to the clinical importance of early detection, diagnosis and treatment of these complications, which will help improve the prognosis of life. At the same time, the influence of DM on musculoskeletal disorders is insufficiently covered in the domestic literature, which was the purpose of this review.